KELAYAKAN EKONOMIS POLITIK UANG DALAM PEMILIHAN JABATAN EKSEKUTIF - Prabowo, Rokh Eddy (Dinamika Ekonomi, 2004)
Money politics is a political behaviour which Lt critl.red by all public. In fact this activity will still always be done although it is critized ly people, since the doer will economically get thetr benefit Mon ey politic, therefore is sull occur in Indonesia in the process of executive election. And send to be a political custom in Indonesia not the Indonesia political culture. By applying the content anaiyus from ike economical point of view, the above tendency may occur for many reasons :1. There is an urgent need.’ ftiological need. 2. Economical value fo having position both executive and legislative instituiion. Based the rule about regional autonomy, the position of regional house of aisembly (DPRD) higher than regional chief having a strong bargaining position from the election time to the periode of this district kead On the other hand. the district head lead the regional governmenL